Assessment of energy and angular dependence of LiF:Mg,Ti dosimeters irradiated in the quantity Hp(0.07) - G. G. Nascimento; C. R. Silva; V. P. Campos; L. L. Campos (Brazilian Journal of Radiation Sciences, 2023)
Radiation dosimetry has the purpose of quantifying the dose received by the occupationally exposed individual. The device used in this process is called a dosimeter, the dosimeter can be used in different situations, for example, the dosimeter used to quantify the dose received in the fingers is the ring model dosimeter, for the extremity, which is the focus of this work. In Brazil, we still do not have standards for the calibration of extremity dosimeters, therefore, in this work, the CASEC recommendations were used, adapted for extremity dosimetry. For a dosimeter to be used in its respective routine, it must present results within some pre-established limits in reference standards. For this purpose, energy dependence and angular dependence tests were carried out. To calibrate the LiF:Mg,Ti thermoluminescent dosimeters, a phantom rod was used. The phantom rod has the function of simulating the region of interest, in the case of this work, the fingers. The dosimeters were irradiated in the magnitude Hp(0.07), with the doses and energies recommended by the CASEC standard. The aim of this work is to characterize end dosimeters in the ring model with LiF:Mg,Ti detectors.